Eel (Anguilla anguilla L. 1758) population structure in the low course of the river Tiber (Latium, central Italy), and preliminary considerations on its contribution to escapement - Capoccioni, F; Costa, C; CICCOTTI, ELEONORA (country:HR, 2007)
European eel (Anguilla anguilla l., 1758) demographic structure was studied in the low course of the river Tiber (Latium, Italy), where a professional fishery targeted to eel has been operating for more than 30 years, with the aim to evaluate its present state in relation to a general decrease of the local stock. this reduction is revealed by the catch contraction following the reduced glass eel recruitment to this river, consistent with what is observed at the continental level. Monthly samplings were carried out from may to november 2006. A total of 454 specimen of Anguilla anguilla were examined in order to assess the developmental stage (on the basis of body colour: yellow eel, silver eel and intermediate), total length, weight and morphometric measures (pectoral fin length, vertical and horizontal eye diameter). A subsample of 229 specimen was sacrificed in order to collect otholits for age evaluation, gonads for sex determination, swimbladders for evaluation of nematode Anguillicola crassus infestation. the developmental classification has been tested by a supervised regression technique, the partial least squares analysis (pls). In order to estimate the Tiber eel population growth curve, age-at-length has been back-calculated by using a linear model regression of the total length on the caudal radius of the otholits. Theoretical growth has been calculated by von bertalanffy’s model. On the whole, eel population structure in the Tiber does not show great changes with respect to previous investigations, contrary to what expected in relation to a possible decrease in population density. The low recruitment level might still be sufficient to sustain eel density and population structure in the low course of the tiber, because fishing effort on juveniles has ceased in the meantime. Some preliminary considerations can be made in relation to the contribution of the tiber eel stock to overall escapement